Obstetric anal sphincter injuries care bundle: innovative approach to improve perineal care in maternity setting - Fatima, Umber; Ajayi, Ifeoluwa; Fayed, Menatalla; Watts, Karen; Sahare, Amita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Perineal injuries during vaginal delivery are a prevalent issue, and obstetric anal sphincter injuries (OASI), which include third and fourth-degree perineal tears, pose significant challenges for maternal health due to potential complications such as faecal incontinence, sexual dysfunction, and impaired quality of life. The OASI care bundle (OASI-CB) was developed in 2015 in response to a concerning rise in the incidence of OASI in the UK. It was implemented in 16 NHS trusts between 2015 and 2017. The results of this implementation were extremely promising, as it was found to significantly reduce the OASI incidence while providing high-quality care to women. Through a comprehensive review of clinical data, patient outcome, and current practice in our unit, we carried out an audit with a goal to meet the standard of the care bundle by improving risk factor identification, improving clinical practices, and offering recommendations to enhance women’s care and further decrease the overall incidence of OASI.